2003
DOI: 10.1556/aagr.51.2003.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cassava genotype, climate and the Bemisia tabaci vector population on the development of African cassava mosaic geminivirus (ACMV)

Abstract: A survey was carried out in the 1996/97 and 1997/98 growing seasons on a field planted in three replicates with five clones of cassava at the International Institute of Tropical Agriculture, Ibadan, located in a transition forest, to determine the effects of cassava genotype and climate on the development of African cassava mosaic geminivirus (ACMV) and changes in the Bemisia tabaci population. Cassava genotype, climate and their interactions have significant (P<0.01) effects on the population of B. tabaci and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…These authors noted afterwards that the level of CMD severity depended on several factors such as the cultivar, climatic conditions, and growing season. According to Abdullahi et al [21], the differences observed in CMD incidence and severity among cassava clones are due to genotypic factors. In the present study, the CMD gravity remained below 21% for improved varieties while reaching 100% for some local varieties at 6 MAP.…”
Section: Discussionmentioning
confidence: 99%
“…These authors noted afterwards that the level of CMD severity depended on several factors such as the cultivar, climatic conditions, and growing season. According to Abdullahi et al [21], the differences observed in CMD incidence and severity among cassava clones are due to genotypic factors. In the present study, the CMD gravity remained below 21% for improved varieties while reaching 100% for some local varieties at 6 MAP.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with previous studies. In fact, several studies conducted on the impact of CMD on cassava in Africa reported that the incidence of this disease varies according to agroecological site, planted varieties, plant age and weather conditions (Abdullahi et al, 2003;Legg et al, 2006;Ntawuruhunga et al, 2007). Arraudeau (1987) suggested that a reduction of nitrogen fertilizer combined with an increase of potassium can limit the effects of CMD.…”
Section: Discussionmentioning
confidence: 99%
“…Since whiteflies are the vectors of CMD, their population on cassava plants were determined in order to assess their relationship with the severity of the CMD disease infection. Direct counts of adult whiteflies on the crop were made as previously described (Hill, 1968;Fargette et al, 1985;Abdullahi et al, 2003).…”
Section: Determination Of Population Of Whiteflymentioning
confidence: 99%